Aberrant DNA Methylation of SEPT9 and SDC2 in Stool Specimens as an Integrated Biomarker for Colorectal Cancer Early Detection - Zhao, Guodong; Liu, Xiaoyu; Liu, Yi; Li, Hui; Ma, Yong; Li, Shiming; Zhu, Yun; Miao, Jin; Xiong, Shangmin; Fei, Sujuan; Zheng, Minxue (Frontiers in Genetics, 2020)
Colorectal cancer (CRC) has become the second leading cause of new cancer cases and the fifth of cancer deaths in China, and early detection is the most effective way to reduce the incidence and mortality of CRC. A number of methylated DNA biomarkers have been found to associate with CRC and precancerous lesions in stool samples, indicating stool methylated DNA biomarkers are potential tools for CRC early detection. In this study, approximately 5 g of stool specimen was collected from 230 subjects (124 in the training set and 106 in the validation set). Stool DNA was extracted and bisulfite-converted, followed by ColoDefense test, a multiplex qPCR assay, that simultaneously detects methylated SEPT9 (mSEPT9) and methylated SDC2 (mSDC2). Youden index was employed to determine the cut-off value of ColoDefense test for stool specimens. In the training set, the optimized cut-off value of stool ColoDefense test was: mSEPT9 analyzed with 3/3 algorithm and mean mSEPT9 Ct values of <38, or mSDC2 with 2/3 algorithm. Stool ColoDefense test achieved Youden indexes of 79.9% and 57.4% in detecting CRC and advanced adenomas (AA), respectively. Its sensitivities in the training set for AA and CRC were 66.7% (95% CI: 24.1-94.0%) and 89.1% (95% CI: 77.1-95.5%) with a 90.8% (95% CI: 80.3-96.2%) specificity, and AUC was 0.956 (95% CI: 0.924 – 0.988). In the validation set, its sensitivities for AA and CRC were 66.7% (95% CI: 24.1-94.0%) and 92.3% (95% CI: 78.0-98.0%) with a 93.2% (95% CI: 82.7-97.8%) specificity, and AUC was 0.977 (95% CI: 0.952 – 1.000). Positive detection rate of stool ColoDefense test has been found to be independent of age, gender, tumor location and tumor size. In conclusion, stool ColoDefense test demonstrated high sensitivities and specificity for the detection of AA and CRC. Therefore, it has the potential to become a low-cost, convenient and highly effective tool for CRC early detection.